Chapter Experiences with beach nourishments on the coast of Alicante, Spain - Pagán, José Ignacio (Proceedings e report, 2020)
The historical evolution of sandy beaches on the coast of Alicante (Spain) has been analysed from aerial images from 1956 to 2019. The beach nourishments carried out in the 1990s to avoid coastal damages and to improve the touristic offer were studied. Shoreline evolution and beach surface has been obtained using GIS. The change of the sediment composition, from gravel to sand, due to the fills has caused a relevant imbalance. Beach nourishments failed its main aim of avoiding the shoreline erosion, causing environmental damages to the nearby Posidonia oceanica meadows.